Introduction - Umberto Margiotta; Juliana Raffaghelli (Pensa MultiMedia, 2015)
The belief of Western world in the universality of the West's values and political systems is naïve and continued insistence on democratization and such "universal" norms will only further antagonize other civilizations. The planetary society needs to reconsider its values, images, symbols, generating from one hand the instruments of tolerance, mutual understanding and dialogue; and from the other, recognizing the common, grounded values of human kind. The main hypothesis, where mainly European Union is investing through its well known policies and programmes, is that education is the key to intervene in conflicting societies within this complex landscape. Too much effort is to be done in the attempt of promoting dialogue among civilizations, preventing people to perceive otherness as a menace; but, at the same time, a long way has already been done in the last sixty years of European reconciliation, and in front of the last thirty years of massive immigration, where intercultural education has played a crucial role.